Consultation for physical illnesses by patients diagnosed and treated for psychiatric disorders by a general practitioner: 20 year follow up study. Issue 6651 (24th September 1988) - Wilkinson, G.; Smeeton, N.; Skuse, D.; Fry, J.
Abstract : Patterns of consultation for physical illness were analysed in a body of consultation data covering a continuous 20 year period from a single general practitioner in south London. Three groups of adult patients were identified: patients with a psychiatric disorder and a new prescription for a psychotropic drug; patients with a psychiatric disorder but no new prescription for a psychotropic drug; and a control group without psychiatric disorder. The percentages of patients having one or more consultation for physical illnesses were stable over the years studied, being roughly 90%, 85%, and 60% respectively. For groups identified in 1972 their patterns of consultation for physical illness were examined in 1957, 1962, and annually from 1967 to 1976. In every year studied except 1957 the group with a psychiatric disorder and a new prescription for a psychotropic drug exceeded both other groups in the percentage of patients having one or more consultations for physical illnesses. Both groups with psychiatric disorders had an excess of consultations over the control group; this excess halved in about four years for the group with a new prescription and in about one year for the group without a new prescription. Mental health care by general practitioners for patients with psychiatric disorders does not seem to have an offset effect on general health care of these patients.